EVACUATION OF CITIZENS AND PROVIDING FIRST AID TO AFFECTED PATIENTS IN THE EVENT OF MAN-MADE ACCIDENTS AT CHEMICAL PLANTS - Z. A. Nurova; Qilichev Ibrohim Fayzullayevich; Baymanov G’olib Shokir o’g’li; Qilichev Jasurbek Fayzullayevich; Qobulov Boburbek Dilshodbek o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
To learn what color is produced when Cl2, NH3, Hydrozin and other toxic substances are produced, what shape and color cloud is formed, and where people should go when there is an accident in chemical industry technologies, i.e. during the production of Cl2, NH3, Hydrogen and other toxic substances.